PREVALENCE, CHEMOTHERAPY AND HAEMATOLOGY OF STRONGYLOSIS IN HORSES OF DISTRICT LAYYAH - K. Mahboob; J. A. Khan; M. S. Khan (Journal of Animal and Plant Sciences, 2008)
The present study had been planned to estimate the infection rate of strongylosis, comparative efficacy of four anti-parasitic drugs; Closantel (Endoectiven), Mebendazole (Vermox), Neem (Azadirachta indica A . Juss) dried leaves and Oxfendazole (Systamex) and effect of strongyloids on different blood parameters in horses of district Layyah. Horses’ faecal samples were processed coprollogically for strongyloids infection with the prevalence of 57.47%. The horses positive for the infestation were randomly divided into six groups A, B, C, D, E and F each comprising of 10 animals. Group A was treated with Closantel (Endoectiven), group B with Mebendazole (Vermox), group C with Neem (Azadirachta indica A. Juss) dried leaves, group D with Oxfendazole (Systamex), group E was kept as positive control (infected untreated) and group F was kept as negative control (uninfected untreated). The percentage efficacy of different treatments was 0 and 0%, 91.93 and 95.16%, 6.89 and 8.62%, 96.82 and 98.14% after days 7 and 14 post medication, in groups A, B, C and D respectively. Horses affected with strongylosis showed greater reduction in haematological parameter. On day zero total erythrocyte count values were 4.50, 4.09, 4.90, 3.85, 3.87 and 8.00 × 106 /μl in group A, B, C, D, E and F, respectively while on day 7 (post treatment) the values were 4.35, 7.47, 5.02, 6.20, 3.78 and 8.00 × 106 /μl in group A, B, C, D, E and F respectively. The values on day 14 (post treatment) were 4.25, 9.10, 5.10, 6.80, 3.69 and 8.00 x 106/μl in group A, B, C, D, E and F respectively. Packed cell volume (PCV) values were 32.50, 31.29, 31.02, 32.80, 32.60 and 37.00% in group A, B, C, D, E and F, respectively on day zero (pre treatment), while the values on day 7 were 31.70, 34.35, 32.10, 36.40, 31.95 and 37.00% in group A, B, C, D, E and F respectively. The values on day 14 (post treatment) in group A, B, C, D, E and F were 31.15, 40.10, 32.12, 39.95, 31.05 and 37.00%, respectively. Haemoglobin estimated values on day zero (pre treatment) in group A, B, C, D, E and F were 8.85, 9.28, 9.35, 9.64, 9.70 and 12.00 g/dl, respectively, while theses values in group A, B, C, D, E and F on day 7 (post treatment) were 8.65, 10.35, 9.45, 11.20, 9.18 and 12.00 g/dl respectively. Similarly the values on day 14 (post treatment) were 8.10, 11.05, 9.49, 12.40, 8.72 and 12.00 g/dl in group A, B, C, D, E and F, respectively.
Keywords: Strongylosis; Strongyloids; Haematology